Tajikistan : Health Sector Note - World Bank (Washington, DC, 2012)
Tajikistan still faces enormous challenges in reversing years of economic decline and political turmoil in addressing the health needs of the population. This report provides a synthesis of the recent trends on the health status of the population and the underlying determinants of health, and the performance of the health system in terms of quality and access to health services. This is followed by a review of Government policies and programs on health reform in the context of its Poverty Reduction Strategy Program, and concludes with a set of recommendations on policies and actions for achieving these objectives. A short-term strategy addressing Tajikistan's urgent public health needs is presented alongside a second, medium-term to longer-term strategy directed at the systemic reforms needed to develop an effective, equitable, and sustainable health system. These recommendations are centered on health financing reform; restructuring of the health delivery system; integration of public health, personal health, and community health services; and strengthening information systems for monitoring and evaluating the impact of the reform policies and programs.